Positioning Technology Education in the Curriculum
VIII, 242 p.
Keywords: The position of technology education in the school curriculum is a topic of continuous discussions. This book offers a number of research-based contributions to that discussion. A number of aspects have been identified that are related to the way technology education can be embedded in the curriculum: The historical development of the subject, its disciplinary character, its relation to other parts of the curriculum, and in particular with science and language education, the relation between the formal school curriculum and informal learning, forms of progression over the grades, and its contribution to citizenship, forms of literacy and ethics. The final chapter deals with specific issues for developing countries. The book can support decision making on the curriculum and the development of technology education as a part of that by providing theoretical and empirical insights on this topic.